Application of Project-Base Learning in Entrepreneurship Education in Indonesia - Pajala, Semuel; Rauf, Rusdiaman; Randy, Muh. Fuad (Jurnal Economic Resource, 2025)
In the process of teaching entrepreneurship education, appropriate pedagogy is needed in realizing a curriculum that is contextual and relevant to the development of information technology and the need for the job market. This research aims to provide a comprehensive overview of entrepreneurship education with effective teaching methods by synthesizing existing research findings. This research method uses a systematic literature review approach to synthesize various academic database literature sourced from Scopus or Web of Science with keywords such as "entrepreneurship education" and "pedagogy", and interviews with teachers of entrepreneurship education courses in Indonesia. The results of the study show that the project-based learning method is very effective in the entrepreneurship education curriculum that follows the development of digital technology and the need for the job market.